Cognitive Conflict Strategy Integrated with Scientific Literacy in Reducing Misconceptions in Chemical Materials - Mumtazah, Rofidatul; Nada, Ella Izzatin; Alawiyah, Nur (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
Abstract: Cognitive Conflict Strategies are Integrated with Scientific Literacy in Reducing Chemical Misconseptions.Problems with students' misconceptions about hydrolysis material still occur frequently, including at Nurul Hayyah High School. Based on the pre-test data, the percentage of misconceptions was 38.42% in the moderate category. If the misconception is not reduced immediately, it will be fatal. As a result, students have difficulty accepting the next material. One learning strategy that can reduce misconceptions is a cognitive conflict strategy combined with scientific literacy. The advantage of the cognitive conflict strategy is being able to reconstruct the understanding that has been attached to students with the new knowledge they receive so that it can reduce the occurrence of misconceptions. The application of learning with cognitive conflict strategies integrated with scientific literacy took place in two meetings. This research is a quantitative research type of pre-experiment model one group pre test-post test design. This study aims to determine the effectiveness of scientific literacy-oriented cognitive conflict strategies in reducing misconceptions about hydrolysis material. The research was conducted at Nurul Hayyah Brebes High School with a research sample of class XI MIPA 2. The sampling technique used was purposive sampling. The data analysis technique used was an analysis of students' misconceptions and interpretation of the results of the questionnaire. The results showed that scientific literacy-oriented cognitive conflict strategies were effective in reducing students' misconceptions about hydrolysis material. This was marked by a decrease in the percentage of students' misconceptions to 13.68% in the low category. In addition, the effectiveness of scientific literacy-oriented cognitive conflict strategies is also marked by positive responses from students with an average percentage of 78% in the good category. Keywords: Misconceptions, Cognitive Conflict, HydrolysisDOI: 10.23960/jppk.v12.i3.2023.06